REKOMENDASI MITIGASI DAERAH RAWAN BANJIR KECAMATAN BALIKPAPAN TIMUR - Hamriani Ryka; Ikhwannur Adha (PETROGAS: Journal of Energy and Technology, 2021)
Flood is a natural event that is difficult to predict because it comes suddenly with an erratic period, especially in East Balikpapan. There are several important factors that cause flooding in South Balikpapan, including the slope, land cover, and rainfall. The purpose of this study was to determine the flood-prone areas of East Balikpapan based on analysis of the factors that cause flooding, such as rainfall, slope, and land cover and give recommended mitigation.In addition, this study is also to obtain the weight of each factor that affects flooding. The data used in this study include digital data on administrative boundaries, rainfall data, digital data on topographic maps, digital data on land use maps, and field observations. The data is processed using an application based on a Geographic Information System (GIS). The overlay process is carried out using ArcGIS and the weighting is obtained from the Analytical Hierarchy Process (AHP) method. The research area has three categories of areas prone to flooding: not prone, vulnerable, and very prone to flooding. Areas that are not prone are 31.2%, vulnerable 0.001%, and very vulnerable 68.7% of the total research area predominantly located in the south of the study area with the dominance of residential land cover. Recommended mitigation recommendations are the arrangement and construction of good irrigation channels, directly connected to the sea, land clearing paying attention to the marbles of the territory and bozem development